تحليل بنود و الإختبار النهاء المعيار المادة اللغاة العربية - Syafi'i; Abu Bakar, M. Yunus; Musthofa; Nadhif, Muhammad Amron; Rahayu, Rizqiyah Ning (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
In learning Arabic at school, there must be an end result. The final result is in the form of questions that are used to determine the final value in learning during their journey. This study aims to analyze the exam or final result in learning Arabic. The goal, so that Arabic language teachers are able to make good measuring tools in measuring student understanding, this study uses a qualitative approach through interviews, observations, with data collection models obtained from student question sheets. then reduce the data, present the data, and draw conclusions to serve as the final conclusion. In the deaf test, this type of written test, the test applied is in the form of multiple choice ytes. In the test there are items in which each question has a choice of answers. In the first question, the teacher asks questions about understanding. So that students do not only know the rules of the Arabic language being studied. In the second question the teacher gives questions that require students to analyze the questions to find answers. However, because this final result test is in the form of multiple choice, students only need to choose the answer asked by the teacher.